خصائص الصداع العنقودي في اللاذقية - لايقة, عيسى; جوني, مطيع; وسوف, مروان (Latakia University Journal -Medical Sciences Series, 2019)
يعدّ الصداع العنقودي أحد الأشكال غير الشائعة للصداع، وغالباً ما يلتبس تشخيصه بغيره من أنواع الصداع ولاسيما الشقيقة وألم مثلث التوائم، و مع ذلك فإن الإعاقة و الكرب اللذان يسببهما الألم الدوري إضافة إلى العلاج النوعي تجعلان من هذا الداء مرضاً عصبياً بالغ الأهمية. شملت الدراسة 25 مريضاً تم تشخيصهم تبعاً للمعايير التشخيصية لجمعية الصداع الدولية ، حيث تم الاستجواب الدقيق و المفصّل للمرضى من خلال توجيه نموذج واحد من الأسئلة. كان الألم في معظمه أحادي الجانب (88%) متوضعاً بشكل أساسي حول الحجاج (90%) والمنطقة الصدغية (62%) و مترافقاً بأعراض ذاتية أشيعها الدماع (88%) و احمرار الملتحمة (82%). بلغت نسبة إصابة الرجال إلى النساء في هذه العيّنة 5.25 : 1 . كما وجدنا قصة عائلية ايجابية عند 4% من المرضى. Cluster headache is one of the uncommon forms of headache and is often mistaken for other types of headache specially migraine and trigeminal neuralgia. However, the disability and distressing of the episodic pain in addition to specific treatment make this disease a very important neurologic problem. Our study includes 25 patients diagnosed with cluster headache according to the International Headache Society. Detailed and precise questioning was performed by asking a standardized form of questions. The pain was almost always unilateral (88%), located essentially around the orbit (90%) and the temporal (62%) and associated with autonomic symptoms. The most common of these symptoms were lacrimation (88%) and conjunctival injection (82%). The male-to-female ratio in this sample was 5.25:1. We found a positive family history in 4% of the patients.